Contemporary Advancement of Consumer Law: An Overview - Srivastava, Surabhi; Thommandru, Abhishek (Department of Marketing Management, Faculty of Commerce and Management Studies, University of Kelaniya, Sri Lanka., 2021)
Off late there is a lot of improvement in consumer protectionism all over the world and now the trend is improving not only in the developed countries but also in the developing and underdeveloped countries. All the legislations that were implemented 30 to 40 years are also being changed as per the latest scenarios in wake of the consumer awareness, ecommerce business models and easy access to grievance and legal aid to the consumers. International organizations and specifically UNGCP (United Nations Guidelines on Consumer Protection) is also are actively involved in providing the updated procedures that are matching the market scenarios and consumer expectations and even monitoring the adoption of these guidelines through respective local legislation by the member states. India has recently revamped its Consumer Protection Act, 1986 and come out with a new act Consumer Protection Act, 2019 notified on 20.07.2020 to come into force, which is not got just an amendment but the entire act itself is repealed and replaced with the new act.
Keywords: Consumer Movement, Consumer Protection, International Convention, Legislations, UNGCP